ISTILAH GAIRAIGO PADA BUKU MANUAL AIRSOFT TYPE 89 OLEH TOKYO MARUI (KAJIAN MORFOFONEMIK) - Muhammad Isfarani (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Modal Intelektual, Universitas Widyatama, 2023)
This research aims to describe the types of gairaigo based on Ishikawa and Rubrecht's theory (2007) and to explain the process of gairaigo formation in accordance with Suzuki's theory (1975) within the manual book of airsoft type 89 by Tokyo Marui, using a morphophonemic approach. This research is of a qualitative descriptive nature, employing the method of translational equivalent analysis. Out of a total of 19 gairaigo data, three types of gairaigo were identified, consisting of 16 instances of direct borrowing, 2 instances of combined abbreviation, and 1 instance of truncation based on the understood reference.Furthermore, in the process of morphophonemic word formation, four processes were identified, including 16 types of phoneme addition, 16 types of phoneme alteration, 7 types of phoneme elision, and 2 types of phoneme truncation. From this analysis, it can be concluded that the direct borrowing type of gairaigo, along with the phoneme addition and alteration processes, were the most frequently encountered.